Towards a Systematic Classification of Methodologies in Islamic Economics - Zatadini, Nabila; Lahuri, Setiawan Bin; Rosyida, Yuniar Fathiyyatur (Journal of Sharia Economics, Banking and Accounting, 2025)
The methodology of Islamic economics currently used tends to adapt from contemporary economics. To address this issue, several Muslim scholars and economists have attempted to develop a methodology for Islamic economics. However, due to the diverse opinions of many Muslim scholars and economists, this methodology remains diverse and has not been systematically codified. To address this issue, this study aims to classify the methodology of Islamic economics based on literature analysis from Muslim economists. The research method used is library research which analyzes the opinions of Muslim economists from journal articles, books, papers, etc. This study found that Muslim economic opinions regarding their main discussion on the methodology of Islamic economics can be divided into four: (1) doctrine; Baqir al-Sadr and Abbas Mirakhor, (2) maqasid sharia; Umer Chapra and Mehmet Asutay, (3) economic problems; A. Mannan, Sabah Eldin Zaim, Akram Khan, Mohammad Aslam Haneef, and Sayyid Tahir, (4) human behavior; Monzer Kahf, Anas Zarqa, and Zub